Diminished Proliferation of Human Immunodeficiency Virus-Specific CD4(+) T Cells Is Associated with Diminished Interleukin-2 (IL-2) Production and Is Recovered by Exogenous IL-2 - Iyasere, Christiana (American Society for Microbiology, 2003)
Virus-specific CD4(+) T-cell function is thought to play a central role in induction and maintenance of effective CD8(+) T-cell responses in experimental animals or humans. However, the reasons that diminished proliferation of human immunodeficiency virus (HIV)-specific CD4(+) T cells is observed in the majority of infected patients and the role of these diminished responses in the loss of control of replication during the chronic phase of HIV infection remain incompletely understood. In a cohort of 15 patients that were selected for particularly strong HIV-specific CD4(+) T-cell responses, the effects of viremia on these responses were explored. Restriction of HIV replication was not observed during one to eight interruptions of antiretroviral therapy in the majority of patients (12 of 15). In each case, proliferative responses to HIV antigens were rapidly inhibited during viremia. The frequencies of cells that produce IFN-γ in response to Gag, Pol, and Nef peptide pools were maintained during an interruption of therapy. In a subset of patients with elevated frequencies of interleukin-2 (IL-2)-producing cells, IL-2 production in response to HIV antigens was diminished during viremia. Addition of exogenous IL-2 was sufficient to rescue in vitro proliferation of DR0101 class II Gag or Pol tetramer(+) or total-Gag-specific CD4(+) T cells. These observations suggest that, during viremia, diminished in vitro proliferation of HIV-specific CD4(+) T cells is likely related to diminished IL-2 production. These results also suggest that relatively high frequencies of HIV-specific CD4(+) T cells persist in the peripheral blood during viremia, are not replicatively senescent, and proliferate when IL-2 is provided exogenously.